Cancer comortality patterns in schizophrenia and psychotic disorders: a new methodological approach for unique databases. Issue 1 (28th January 2014) - Ajdacic‐Gross, Vladeta; Tschopp, Alois; Bopp, Matthias; Gutzwiller, Felix; Rössler, Wulf
Abstract The aim of this study was to determine the pattern of cancer comortality in deaths registered with schizophrenia and psychotic disorders. It focused on the question of whether the proportions of different types of cancer diverge when they are co‐registered with schizophrenia/psychotic disorders or with other causes of death in mortality statistics. We developed an analysis approach applicable to common mortality statistics data when no linkage with morbidity databases or other registers is possible. The analysis covered Swiss mortality data from a 39‐year period (1969 − 2007) and was confined to the most frequent cancers. We applied a two‐step case‐control analysis with bootstrapping (1000 repetitions). The cases were defined by the cancer‐schizophrenia registrations for each specific cancer, whereas the controls were matched from the remaining cases (matching criteria: sex, age, region, subperiod). Cancers with deviant standardized mortality ratios (SMRs) included stomach cancer (1.6; 2.2 after reweighting), lung cancer (0.8; 0.5 after reweighting) and breast cancer (1.6; 1.5 after reweighting). The comortality pattern of cancers in schizophrenia and psychotic disorders diverges from the pattern found in other co‐registered causes of death. The relatively low frequency of lung cancers is particularly paradoxical in view of the smoking habits of schizophrenia patients. Copyright © 2014 John Wiley & Sons, Ltd.